NOx Minimization in Staged Combustion Using Rich Premixed Flame in Porous Media. Issue 9 (1st September 2020) - Banerjee, Abhisek; Kundu, Prithwish; Gnatenko, Vitaliy; Zelepouga, Serguei; Wagner, John; Chudnovsky, Yaroslav; Saveliev, Alexei
ABSTRACT: Two-stage combustion of methane/air is studied experimentally and numerically with a focus on achieving ultralow NOx emissions. The primary flame is a rich premixed flame in the porous medium. The flame is stabilized in the range of equivalence ratios from 1.1 to 1.7 using upstream heat extraction. The products of the primary flame are rich in the partial oxidation and reforming products such as CO, H2, and CH4 . Due to the self-regulated heat losses from the flame the maximum flame temperature of the primary flame remains close to 1700 K. The rich-flame environment and low-flame temperatures limit NOx formation in the primary flame. The NOx emission index of the primary flame shows a maximum at the equivalence ratio of 1.1 and reduces for richer mixtures. The products of the primary flame are burned in the secondary nonpremixed flame. The products could be intercooled to reduce temperature and minimize NOx formation in the secondary nonpremixed flame. The emission index of the secondary flame increases with the equivalence ratio. Variation of combined emission index shows a minimum value at the equivalence ratio of 1.2. The trend remains consistent with the intercooling of the primary flame products.